NKCC1 deficiency in forming hippocampal circuits triggers neurodevelopmental disorder: Role of BDNF-TrkB signalling - Szymanski, J; Minichiello, L (MDPI, 2022)
The time-sensitive GABA shift from excitatory to inhibitory is critical in early neural circuits development and depends upon developmentally regulated expression of cation-chloride cotransporters NKCC1 and KCC2. NKCC1, encoded by the SLC12A2 gene, regulates neuronal Cl− homeostasis by chloride import working opposite KCC2. The high NKCC1/KCC2 expression ratio decreases in early neural development contributing to GABA shift. Human SLC12A2 loss-of-function mutations were recently associated with a multisystem disorder affecting neural development. However, the multisystem phenotype of rodent Nkcc1 knockout models makes neurodevelopment challenging to study. Brain-Derived Neurotrophic Factor (BDNF)-NTRK2/TrkB signalling controls KCC2 expression during neural development, but its impact on NKCC1 is still controversial. Here, we discuss recent evidence supporting BDNF-TrkB signalling controlling Nkcc1 expression and the GABA shift during hippocampal circuit formation. Namely, specific deletion of Ntrk2/Trkb from immature mouse hippocampal dentate granule cells (DGCs) affects their integration and maturation in the hippocampal circuitry and reduces Nkcc1 expression in their target region, the CA3 principal cells, leading to premature GABA shift, ultimately influencing the establishment of functional hippocampal circuitry and animal behaviour in adulthood. Thus, immature DGCs emerge as a potential therapeutic target as GABAergic transmission is vital for specific neural progenitors generating dentate neurogenesis in early development and the mature brain.